Les archives à l’épreuve du temps : les recadrements temporels des courts métrages de la série Souvenir - Huberman, Isabella (Canadian Journal of Film Studies, 2020)
This article examines how “colonial time” is called into question in two short films of the National Film Board of Canada’s series Souvenir, from 2015. The question of time lies at the heart of this series, for which the NFB commissioned contemporary Indigenous filmmakers to take up their archives of visual material on Indigenous peoples. The colonial temporal framework is at work in the vast archives of ethnographic and documentary film and photography on Indigenous peoples dating back to the early twentieth century, in which Indigenous people are often represented as part of “vanishing” cultures. Thus, in this article, I underscore the temporal interruptions that occur when ethnographic visual material of Indigenous peoples is put into the hands of contemporary Indigenous artists. I focus first on what it means to repurpose dehumanizing colonial archives and ask whether visual sovereignty is in fact possible within the archives. By analyzing the reappropriation of archival footage in the short films Mobilize by Caroline Monnet and Etlinisigu’niet (Bleed Down) by Jeff Barnaby, I elucidate how the filmmakers break with modes of colonial time through what I propose to call “reframings” that offer alternative ways of conceiving of time. By rehabilitating ethnographic images, these filmmakers refuse to project the material into the distant past and complicate the readability of Indigenous images in the archives, revealing how the reappropriation of old images can be just as powerful as the production of new ones.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous Sovereignty and Settler Amnesia: Robert Houle's "Premises for Self Rule" - Ernst, Stacy A. (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Le modernisme en art est souvent considéré comme un développement spécifiquement occidental. Robert Houle, l'artiste, écrivain et commissaire d'exposition d'origine Saulteaux, a cependant toujours soutenu que sa propre pratique est moderniste et qu'elle suit une filiation esthétique autochtone. Cet article s'intéresse particulièrement à une œuvre produite par Houle en 1994, Premises for Self Rule, dans laquelle l'artiste a juxtaposé des textes de législation coloniale à des panneaux peints en monochrome et des cartes postales trouvées en archives. Il propose qu'à travers cette stratégie de rapprochement, l'artiste fusionne la tradition de la peinture de parflèche à l'esthétique moderniste, remettant ainsi en lumière la négociation interculturelle, l'amnésie coloniale, ainsi que les écarts qui séparent les épistémologies et traditions artistiques des peuples autochtones et allochtones
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; _Nettoyé

From Great-Grandmothers to Great-Granddaughters: "Moving Life" in Baby Carriers and Birchbark Baskets - Kahsenni:io Nahwegahbow, Alexandra (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Les porte-bébés et les paniers d'écorce autochtones sont, en tant que réceptacles, conçus pour porter et tenir. Outre cette fonction, ils sont aussi détenteurs d'histoires, de mémoire, et de liens familiaux. Créés individuellement et ornementés avec soin, ces objets constituent une sorte de portrait des femmes qui les ont produits, ainsi que des générations qui ont hérité des pratiques et des motifs servant à les fabriquer. En élargissant la définition de la notion de portrait de famille, cet article considère deux objets provenant de Bear Island, en Ontario. Le premier est un porte-bébé ayant appartenu à Madeline Katt Theriault, et le deuxième est un panier d'écorce vraisemblablement créé parson arrière-grand-mère Angele Katt. Par leur parenté, ces réceptacles englobent une histoire multigénérationnelle qui s'étend de l'arrière-grand-mère à son arrière-petite-fille
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Archival Predecessors and Indigenous Modernisms: Archives in Contemporary Curatorial Practice on the Northwest Coast - Kisin, Eugenia (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Les projets d'expositions archivistiques—et leur documentation—sont des lieux de production de connaissances en histoire de l'art, ainsi que des interventions politiques, qui placent les documents dans un autre contexte afin d'interroger les canons et les façons de voir des colonialistes-colons. À partir de ces relations discursives, visuelles et archivistiques, cet article examine deux rétrospectives solos des œuvres sculptées et peintes des artistes modernistes kwakwaka'wakws, Doug Cranmer ('Namgis) et Henry Speck (Tlawit'sis), présentées à Vancouver en 2012. En considérant comment les conservateurs ont fait appel aux archives familiales intimes et à des documents du domaine public, il traite de l'utilité des archives du modernisme pour activer des liens affectifs, ancestraux et familiaux au-delà des modes de compréhension canoniques et historiques des mouvements esthétiques et des contextes de production
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Les arts wendats au service de la diplomatie et de la traite - de Stecher, Annette (Recherches amérindiennes au Québec, 2014)
Cet article porte sur les oeuvres artisanales des femmes wendates du xix ₑ siècle dans le contexte plus large des traditions des arts visuels wendats. En plus des objets commerciaux, l’auteure présente des objets faits pour être utilisés lors d’occasions cérémonielles et rituelles spéciales, et qui avaient aussi une valeur importante dans la communauté. Ces deux catégories d’artisanat dévoilent la façon dont les femmes wendates adaptaient leurs traditions artistiques aux sphères économiques et diplomatiques du monde colonial, et ce avec grand succès. Ces arts ont aidé la communauté à conserver une vision du monde amérindienne et ont préservé des traditions culturelles qui se sont perpétuées d’une génération à l’autre, tout en intégrant des innovations créatives. Ils démontrent aussi le rôle diplomatique important joué par les oeuvres présentées aux dignitaires eurocanadiens et européens dans un contexte cérémoniel, afin d’établir et de maintenir des relations politiques et économiques harmonieuses.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

The Art of Community - de Stecher, Annette (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
La nation huronne-wendat de Wendake (Lorette, Québec) a maintenu sa culture et son identité pendant des siècles, souvent en dépit de, et en résistance contre les pressions occasionnées par la présence missionnaire et les politiques coloniales. Cette survivance est tributaire de savoirs, de valeurs et de coutumes transmis de génération en génération. Cet article explore l'art de la communauté wendat et ses éléments constitutifs : la fabrication d'objets, la tradition orale, l'engagement actif des membres de la collectivité dans les pratiques traditionnelles, ainsi que l'adaptation des pratiques ancestrales aux préoccupations actuelles. Il montre comment la production artistique wendat, dans sa force expressive, contribue à la continuité et cohésion sociale de la nation wendat.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Anthem: perspectives on home and native land - Rice, Ryan (Carleton University Art Gallery = Galerie d'art de l'Université Carleton, 2008)
Eight artists from across Canada create works identify varying forms of nationhood that either serve or detract from the concept of a national accord. Each artist explores the idea of ₃anthem₄ through a wide-angle lens, broadening the national discourse to include not only colonial histories, but also distinctive and multicultural liberties that take various forms: treaties, blood, languages, sexual orientation, faith, and oral traditions. The dynamic range of art works exhibited contribute to a more inclusive national narrative and expose and accept the diverse forms of nationalism that exist across the country.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Kwah í:ken tsi Iroquois - Rice, Ryan (Ottawa Art Gallery = Galerie d'art d'Ottawa, 2008)
Catalogue d'exposition avec des textes de Ryan Rice, Françoise Charron, Emily Falvey et Hilda Nicholae.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Hochelaga revisité = Hochelaga revisited - Rice, Ryan (MAI (Montréal, arts interculturels), 2009)
Catalogue d'exposition avec des textes de Ryan Rice; Jason Baerg; Lori Blondeau; Martin Loft; Cathy Mattes; Nadia Myre; Ariel Lightningchild Smith.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Presence and Absence Redux: Indian Art in the 1990s - Rice, Ryan (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Les années 1990 sont une décennie cruciale pour l'avancement et le positionnement de l'art et de l'autonomie autochtones dans les récits dominants des états ayant subi la colonisation. Cet article reprend l'exposé des faits de cette période avec des détails fort nécessaires. Pensé comme une historiographie, il propose d'explorer chronologiquement comment les conservateurs et les artistes autochtones, et leurs alliés, ont répondu et réagi à des moments clés des mesures coloniales et les interventions qu'ellesontsuscitéesdu point de vue politique, artistique, muséologique et du commissariat d'expositions. À la lumière du 150e anniversaire de la Confédération canadienne, et quinze ans après la présentation de la communication originale au colloque, Mondialisation et postcolonialisme: Définitions de la culture visuelle v, du Musée d'art contemporain de Montréal, il reste urgent de faire une analyse critique des préoccupations contemporaines plus vastes, relatives à la mise en contexte et à la réconciliation de l'histoire de l'art autochtone sous-représentée.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Déni et ignorance de l'historicité autochtone dans l'histoire de l'art occidentale - Uzel, Jean-Philippe (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Western art history long refused to recognize the historicity of Indigenous art, seeing it instead as a "primitive" mode of human expression. While the dynamism of Indigenous creation since the 1960s has made such an assertion impossible, the institutional recognition given contemporary Indigenous art in the art world is paradoxically accompanied by a lack of critical and theoretical analysis. Today, there is a genuine ignorance concerning Indigenous conceptions of history-their "regime of historicity"-on the part of Western art historians. This is all the more surprising given the recent "temporal turn" taken by the discipline, which emphasizes the question of mixed temporalities without acknowledging it as an essential dimension of Indigenous art. This paper revisits Western art history's long-standing denial of the historicity of Indigenous art, and then considers its current disregard for the ways Indigenous art allows different forms of temporality to coexist. The underlying thesis of the essay is that today's disinterest is, in fact, a prolongation of yesterday's denial.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Art of the Northwest Coast - Jonaitis, Aldona.. (University of Washington Press, 2006)
"Art of the Northwest Coast is a comprehensive survey of the Native arts of the Pacific Northwest Coast, spanning the region from Puget Sound to Alaska, and proceeding from prehistoric times to the present. Incorporating the region's social history with the observations of anthropologists, historians of art, and Native peoples, this rich, vibrant book reveals how a complex web of factors informed these groups' varied responses to the changes and challenges brought about by contact with Europeans."-
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Figurative Repatriation First Nations ‘Artist-Warriors’ Recover, Reclaim, and Return Cultural Property through Self-Definition - Kramer, Jennifer (Journal of Material Culture, 2004)
This article begins with an analysis of the problems of ‘physical repatriation’, as I review the case of the return of a First Nations mask to its community of origin. First Nations struggle to fit their concepts of ownership into western ones, where objects are viewed as alienable. As an alternative, the art of John Powell and Marianne Nicolson depicts a ‘figurative repatriation’ that does not rely on either the courts or museums to recognize legal or moral ownership. I argue that these contemporary artworks are social agents, which bring First Nations cultural objects home by staking out territory within museums. These ‘artist warriors’ forcibly recover (both literally and metaphorically) First Nations objects on display in foreign settings and reinscribe meaning at the level of the personal and the communal. They make objectified assertions of native identity that reclaim the right to self-definition. Moreover, these claims are made all the more powerful through their conscious location within an oppositional discourse framed by the Canadian western art world.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; _Nettoyé

Native Art of the Northwest Coast: A History of Changing Ideas - Townsend-Gault, Charlotte; Kramer, Jennifer (UBC Press, 2013)
This remarkable volume, many years in the making, records and scrutinizes definitions of Northwest Coast Native art and its boundaries. A work of critical historiography, it makes accessible for the first time in one place a broad selection of more than 250 years of writing on Northwest Coast "art." Organized thematically, its excerpted texts are from both published and unpublished sources, some not previously available in English. They cover such complex topics as the clash between oral and written knowledge, transcultural entanglement, the influence of surrealist thinking, and the long history of the deployment of Northwest Coast Native art for nationalist purposes. The selections are preceded by thought-provoking introductions that give historical context to the diverse intellectual traditions that have influenced, stimulated, and opposed each othe
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Unsettling Native Art Histories on the Northwest Coast - Bunn-Marcuse, Kathryn B.; Jonaitis, Aldona (Native art of the Pacific Northwest : a Bill Holm Center series, 2020)
"This edited collection focuses on "unsettling" Northwest Coast art studies, bringing forward voices that uphold Indigenous priorities, engage with past and ongoing effects of settler colonialism, and advocate for practices for more accountable scholarship. Featuring authors with a variety of perspectives, backgrounds, and methodologies, Unsettling Art Histories offers new insights for the field of Northwest Coast art studies. Key themes include discussions of cultural heritage protections and long-standing defenses of natural resources and territory; re-centering women and the critical role they play in transmitting cultural knowledge across generations through materials, techniques, and creations; reflecting on the decolonization work being undertaken in museums; and examining how artworks function beyond previous scholarly framings as living documents carrying information critical to today's inquiries. Re-examining previous scholarship and questioning current institutional practices by prioritizing information gathered in Native communities, the essays in this volume exemplify various methods of "unsettling" and demonstrate how new methods of research have reshaped scholarship and museum practices."
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Art for a New Understanding: Native Voices, 1950s to Now - Hopkins, Candice; Well-Off-Man, Manuela; Besaw, Mindy N.; Crystal Bridges Museum of American Art (University of Arkansas Press, 2018)
"Art for a New Understanding, an exhibition from Crystal Bridges Museum of American Art that opened in October 2018, seeks to radically expand and reposition the narrative of American art since 1950 by charting a history of the development of contemporary Indigenous art from the United States and Canada, beginning when artists moved from more regionally-based conversations and practices to national and international contemporary art contexts. This accompanying book documents and expands on the histories and themes of this exciting exhibition. This fully illustrated volume includes essays by art historians and historians and reflections by the artists included in the collection. Also included are key contemporary writings--from the 1950s onward--by artists, scholars, and critics, investigating the themes of transculturalism and pan-Indian identity, traditional practices conducted in radically new ways, displacement, forced migration, shadow histories, the role of personal mythologies as a means to reimagine the future, and much more. As both a survey of the development of Indigenous art from the 1950s to the present and a consideration of Native artists within contemporary art more broadly, Art for a New Understanding expands the definition of American art and sets the tone for future considerations of the subject. It is an essential publication for any institution or individual with an interest in contemporary Native American art, and an invaluable resource in ongoing scholarly considerations of the American contemporary art landscape at large."
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Mapping Modernisms: Art, Indigeneity, Colonialism - Harney, Elizabeth; Phillips, Ruth B. (Ruth Bliss) (Objects/histories : critical perspectives on art, material culture, and representation, 2018)
Mapping Modernisms" brings together scholars working around the world to address the modern arts produced by indigenous and colonized artists. Expanding the contours of modernity and its visual products, the contributors illustrate how these artists engaged with ideas of Primitivism through visual forms and philosophical ideas. Although often overlooked in the literature on global modernisms, artists, artworks, and art patrons moved within and across national and imperial borders, carrying, appropriating, or translating objects, images, and ideas. These itineraries made up the dense networks of modern life, contributing to the crafting of modern subjectivities and of local, transnationally-inflected modernisms. Addressing the silence on indigeneity in established narratives of modernism, the contributors decenter art history's traditional Western orientation and prompt a re-evaluation of canonical understandings of twentieth-century art history. 'Mapping Modernisms' is the first book in Modernist Exchanges, a multivolume project dedicated to rewriting the history of modernism and modernist art to include artists, theorists, art forms, and movements from around the world."
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; _Nettoyé

Transforming Images: The Art of Silver Horn and His Successors - Berlo, Janet Catherine; Donnelley, Robert G; Green, Candace S (David and Alfred Smart Museum of Art, University of Chicago, 2001)
Silver Horn's art documents the changes in the lives of the Kiowa Indians, as well as changes in Kiowa art itself. The art presented here, shows the bridge he created between ancient Kiowa aesthetics and modern forms of expression that had an impact on younger Native American artists.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

The Early Years of Native American Art History: The Politics of Scholarship and Collecting - Berlo, Janet Catherine (ACLS Humanities E-Book, 1992)
This collection of essays deals with the development of Native American art history as a discipline.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Amérique du Nord: arts premiers - Berlo, Janet Catherine; Phillips, Ruth B. (Terre indienne, 2006)
Replaçant chaque oeuvre dans son contexte familial, social, géographique, économique et spirituel, cet album présente l'art des peuples premiers d'Amérique du Nord, des Inuits aux peuples des déserts du sud-ouest des Etats-Unis, des origines à la période contemporaine
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Figure de l’indiscipline. Domingo Cisneros, un parcours artistique atypique - Pageot, Edith-Anne (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Between 1974 et 1996, the Canadian artist of Mexican origin Domingo Cisneros was seen as a leading figure in contemporary art in Canada. He played a major role in the process of self-determination that First Nations artists undertook following the infamous 1969 White Paper, the Statement of the Government of Canada on Indian Policy. Cisneros was recognized both in the Native and Quebec francophone contemporary art worlds, and was internationally acclaimed within the conceptual and contextual art milieu gathered around the Polish artist Jan Swidzinski. His contribution has nevertheless been forgotten. Coinciding with his seventy-fifth birthday, this article aims to review, conceptually frame, and contextualize Cisneros’s role and impact on the Canadian art scene. It argues that his interdisciplinarity, or “indiscipline,” was instrumental in building connexions and bridges between heterogeneous values, cultural protocols, and epistemological principles.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Pour une autohistoire amerindienne: essai sur les fondements d'une morale sociale - Sioui, Georges E (Presses de l'Université Laval, 1999)
Sioui has produced a work not only of metahistory but of moral reflections. He contrasts Euroamerican ethnocentrism and feelings of racial superiority with the Amerindian belief in the "Great Circle of Life" and shows that human beings must establish intellectual and emotional connections with the entire living world if they hope to achieve abundance, quality, and peace for all. Sioui is proud to be a Huron and an Amerindian and is fully aware of the injustices that the aboriginal people of North America have suffered - and continue to suffer - at the hands of Euroamericans. He is convinced that the greatness of Amerindians does not lie only in the past but that Native peoples will play an even more important role in the future by providing ideas essential to creating aviable way of life for North America and the world. While this is a polemical work, Sioui never descends to recrimination or vituperative condemnation, even when that might seem justified. Instead, he has given us a polemic that is written at the level of philosophy.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; _Nettoyé

Zacharie Vincent: une autohistoire artistique - Vigneault, Louise (Éditions Hannenorak, 2016)
"Qui était Zacharie Vincent, aussi connu, à l'époque, sous le nom de Tehariolin? Peu de gens le savent. Il s'agit pourtant d'une figure incontournable, considérée comme le premier peintre autochtone moderne. Le présent ouvrage, signé par l'historienne de l'art Louise Vigneault, lève donc le voile sur ce peintre et chef de guerre wendat, longtemps tombé dans l'oubli, qui a considérablement marqué le 19e siècle. Zacharie Vincent (1815-1886) a suscité la fascination, avec ses allures d'artiste bohème, sa dégaine de clochard mêlée à ses ornements d'apparat, la singularité de ses autoportraits. La légende entourant celui que l'on appelait le " dernier des Hurons " a attiré les regards sur la petite communauté de la Jeune-Lorette (aujourd'hui Wendake), pour ensuite révéler la fierté et la résilience du peuple wendat. Des peintres canadiens, tels Antoine Plamondon et Eugène Hamel, ont réalisé des portraits de Vincent, puis des photographes comme Louis-Prudent Vallée ont immortalisé son image. Zacharie Vincent : une autohistoire artistique nous plonge au cour de la vie et de l'ouvre d'un artiste énigmatique qui a laissé en héritage des témoignages essentiels sur sa nation, en équilibre entre la tradition et la modernité."-- Quatrième de couverture
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

La "monnaie des Sauvages": les colliers de wampum d'hier à aujourd'hui - Lainey, Jonathan C. (Septentrion, 2004)
« Tantôt présents ou documents figurés, tantôt considérés comme de la monnaie, les wampums sont des colliers de perles fabriquées de coquillages marins qui étaient utilisés par les Indiens du Nord-Est de l'Amérique et les Européens. Si des milliers de wampums sont cités dans les archives coloniales, peu d'entre eux sont parvenus jusqu'à nous et la tradition de leur échange a depuis longtemps cessé d'être pratiquée. Les wampums du Musée de la civilisation de Québec ont été acquis à la fin du XIXe siècle dans un contexte particulier où collectionneurs et numismates s'arrachaient les objets amérindiens et où ceux-ci, pour diverses raisons, acceptaient de s'en départir. Cette collection n'avait jamais été étudiée, ni par les historiens, ni par les ethnologues ou par les muséologues. Par un raisonnement critique, en avançant toujours avec prudence et sans jamais céder à la simplification, Jonathan C. Lainey soulève les difficultés et les problèmes reliés à leur étude et à leur interprétation. Il reconstitue méticuleusement les différentes étapes de la vie des objets, leur muséification et le sens qu'on peut leur donner aujourd'hui. Plus qu'une simple étude sur les wampums, cet ouvrage a le mérite de porter un regard sur certaines réalités historiques relatives à la culture matérielle d'un groupe amérindien de la région de Québec, les Hurons de Lorette. Ce sont le rapport à l'Autre, les processus d'appropriation et les transferts culturels qui sont abordés par l'étude de la transformation de l'usage des wampums, devenus aujourd'hui objets de musée. Reposant sur une ethnographie et une iconographie riches et détaillées, ce livre constitue une contribution importante aux études ethnohistoriques et aux études amérindiennes de l'Amérique du Nord-Est. »-- Résumé de l'éditeur.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; _Nettoyé

La crise d'Oka en récits: territoire, cinéma et littérature - St-Amand, Isabelle (Collection InterCulture, 2015)
La crise d'Oka marque un véritable moment de rupture dans lesrelatlons entre les premiers peuples et les colonies de peuplement. Dans les suites immédiates de l’échec de l’accord du lac Meech, ce long siège armé de 78 jours rend visible une présence autochtone que les sociétés québécoise et canadienne avaient imaginée évanouie. Àl’inverse, l’opposition à l’empiétement mis en œuvre à Kanehsatàke età Kahnawàke réactive une longue histolre de résistance au projet colonial d'appropriation des terres et d'effacement des peuples autochtones. Ce livre envisage la crise d'Oka, ou la résistance à Kanehsatàke, comme un espace de focalisatlon où se donne à voir larelation globale entre les peuples. Qu'est-ce que l'événement fait surgir, transforme et crée, dans la scénographie du siège, mais aussi dans les films documentaires et les récits littéraires, autochtones et allochtones? À l'heure où une nouvelle génération revient sur cette crise politique aux enjeux non résolus, ce livre ouvre un espace où entrent en relation et s'affrontent différents intérêts, connaissances et expressions relatifs à ce conflit territorial. Il engage une réflexion épistémologique essentielle à un processus de décolonisation aussi impératif qu'exigeant.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Sites of Aboriginal Difference: A Perspective on Installation Art in Canada - Collins, Curtis J (2002)
"This dissertation traces the presence of installation-based practices among artists of Aboriginal ancestry via selected exhibitions across Canada. It begins with a methodological perspective on Canadian art history, federal law, and human science, as a means of establishing a contextual backdrop for the art under consideration. The rise of an Indian empowerment movement during the twentieth century is then shown to take on an international voice which had cultural ramifications at the 1967 Canadian International and Universal Exhibition. Nascent signs of a multi-mediatic aesthetic are distinguished in selected works in Canadian Indian Art '74, as well as through Native-run visual arts programs. First Nations art history is charted via new Canadian art narratives starting in the early 1970s, followed by the development of spatial productions and hybrid discourses in New Work By a New Generation in 1982, and Stardusters in 1986. The final chapter opens with a history of installation art since the Second World War, as related to the pronounced presence of multi-mediactic works in Beyond History in 1989. Post-colonial and postmodern theories are deployed to conclusively situate both the artistic and political concerns featured throughout this study, and lead into the analysis of selected installations at Indigena: Contemporary Native Perspectives and Land, Spirit, Power: First Nations at the National Gallery of Canada. These 1992 shows in the national capital region ultimately confirm the maturation of a particular socio-political aesthetic that tested issues of Canadian identity, while signifying Aboriginal sites of difference."--
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Zacharie Vincent et ses héritiers - Vigneault, Louise (Inter, 2016)
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Repenser le temps et l'espace, du wampum au selfie - Vigneault, Louise (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
This article considers the way certain Indigenous artists are reviving conceptions of territory and history that are anchored in secular epistemologies and the construction of knowledge. Such conceptions provide a way for these artists to respond to colonial appropriation, reactivate interrupted dialogues, engender new forms of territorialization, and create places of commemoration and memory preservation. Similar to the historiographical deconstruction performed by thinkers and activists such as Vine Deloria Jr. and Taiaiake Alfred, these artists’ works offer a model of autonomy and environmental balance. While some are reviving mnemonic practices, such as the making of wampum, which traditionally preserve memories of alliances and conflicts, others have embraced Internet and selfie technologies as a means of creating new spaces for speech and recognition
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Exposer, diffuser, faire entendre sa voix: présence de l'art contemporain autochtone au Québec entre 1967 et 2013 - De Lacroix, Pricile (Université du Québec à Montréal, 2017)
Ce mémoire se penche sur la diffusion de l'art contemporain autochtone au Québec de 1967 à 2013. Grâce à un corpus constitué de 640 expositions comprenant au moins un artiste des Premières Nations, métis ou inuit s'étant tenues quelque part dans la province à l'intérieur de ces 46 années, il a été possible de dresser un portrait global raisonné de ce qui s'est fait – ou ne s'est pas fait – concrètement, au-delà des a priori maintes fois reconduits. Il démontre, par exemple, que la décennie 1990 n'a pas été si « désertique » qu'il n'y parait, mais que la période 2000-2013, malgré son apparente vigueur, cache plusieurs dynamiques à l'œuvre au Québec rendant la reconnaissance et l'intégration des artistes autochtones dans le grand réseau des arts contemporains encore difficile. Ce mémoire apporte un éclairage sur le rôle marquant joué par les réseaux parallèles dans la diffusion de l'art contemporain autochtone, celui, parfois novateur, joué par les musées d'histoire et d'ethnographie ainsi que par les musées au sein même des communautés autochtones, puis la fermeture bien visible des institutions d'art du Québec jusqu'au milieu des années 2000. Il met également en lumière la présence de solitudes existantes au Québec, c'est-à-dire celle qui opère une division entre les artistes autochtones francophones et anglophones, favorisant grandement ces derniers, ainsi qu'entre artistes autochtones versus allochtones, les deux se mélangeant encore difficilement au sein des expositions. Enfin, ce mémoire permet de constater qu'en quatre décennies, le nombre d'artistes autochtones pratiquant de manière professionnelle au Québec n'a cessé d'augmenter, que Montréal s'est inscrite de plus en plus comme une métropole pouvant attirer des artistes autochtones de calibre national et international, que certaines régions du Québec, comme le Saguenay et l'Abitibi, ont, contrairement à d'autres, fait preuve d'une ouverture certaine face à l'art autochtone, mais également qu'il y a eu – et qu'il y a peut-être encore – une corrélation entre événements festifs et expositions accrues d'art contemporain autochtone, ce qui a tendance à le garder dans le domaine du folklore au Québec, et nuire véritablement à la reconnaissance des artistes professionnels.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Rituels, mort et renaissance. Une redécouverte de l’artiste huron-wendat Pierre Sioui - De Lacroix, Pricile (Frontières, 2018)
Le travail de l’artiste huron-wendat Pierre Sioui est assez méconnu au Québec. Prolifique dans les années 1980 et ayant exposé aux quatre coins du Canada ainsi qu’aux États-Unis, Sioui a ensuite totalement disparu du milieu des arts contemporains autochtones. Une relecture du travail de cet artiste permet de redécouvrir un créateur fascinant tout à fait inscrit dans les préoccupations esthétiques et politiques de sa décennie. Sioui semble surtout avoir employé sa démarche artistique au service d’une redécouverte de son identité et de ses racines. Il l’a fait par le biais de recherches à la fois théoriques, cosmologiques et esthétiques des valeurs et de la culture huronne, le conduisant vers une thématique entourant principalement le sens des rituels, la mort et le cycle de la vie. Tous ces vieillards dans ses oeuvres, ces cadavres, ces ossements et ces crânes, parlent de relations entre mort et renaissance, entre colonialisme puis réappropriation, et semblent être pour Sioui une véritable trame créatrice à renouveler sans cesse.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Whose Land Is It Anyway?: A Manual for Decolonization - McFarlane, Peter; Schabus, Nicole (Fédération of Post-Secondary Education of BC, 2018)
Whose Land Is It Anyway? A Manual for Decolonization provides a variety of Indigenous perspectives on the history of colonialism, current Indigenous activism and resistance, and outlines the path forward to reconciliation. This audio version features renowned Indigenous writers Taiaiake Alfred, Glen Coulthard, Russell Diabo, Beverly Jacobs, Melina Laboucan-Massimo, Kanahus Manuel, Jeffrey McNeil-Seymour, Pamela Palmater, Shiri Pasternak, Nicole Schabus, Senator Murray Sinclair, and Sharon Venne. The late Arthur Manuel’s writings are read by his grandson, Mahekan Anderson.
Keywords: 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

“I Want to Call Their Names in Resistance”: Writing Aboriginal Women into Canadian Art History. - Farrell Racette, Sherry (Rethinking Professionalism: Essays on Women and Art in Canada, 1850-1970, 2012)
As bell hooks points out in “Aesthetic Inheritances: History Worked by Hand,” writing an inclusive art history is no easy task. Until very recently, Aboriginal women have been written out of Canadian art history, or rather art history has been written around us. How do we write ourselves in? It falls far beyond simple insertion; the erasures are far too deep. Insertion presumes a simple forgetfulness, an oversight, a neglecting of the obvious. Insertion assumes a presence. It implies a shared mode of history, a common belonging to a collective archive, and an agreed-upon understanding of what it means to be an artist. Beyond the important considerations of race, gender, culture, and social class, our distinct legal status in Canada must be acknowledged. This was particularly true for women artists working between 1880 and 1970. For much of the time period under consideration, First Nations communities lived under a profoundly restrictive regime of colonial power. Relationships between First Nations people and the Canadian state have been defined by the Indian Act, a piece of legislation enacted in 1876 and surviving, through many amendments and revisions, until the present time.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Returning Fire, Pointing the Canon: Aboriginal Photography as Resistance - Farrell Racette, Sherry (The Cultural Work of Photography in Canada, 2011)
Résumé livre : The Cultural Work of Photography in Canada is an in-depth study on the use of photographic imagery in Canada from the late nineteenth century to the present. This volume of fourteen essays provides a thought-provoking discussion of the role photography has played in representing Canadian identities. In essays that draw on a diversity of photographic forms, from the snapshot and advertising image to works of photographic art, contributors present a variety of critical approaches to photography studies, examining themes ranging from photography's part in the formation of the geographic imaginary to Aboriginal self-identity and notions of citizenship. The volume explores the work of photographs as tools of self and collective expression while rejecting any claim to a definitive, singular t... Source: Publisher
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

‘Enclosing Some Snapshots’: James Patrick Brady, Photography, and Political Activism - Farrell Racette, Sherry (History of Photography, 2018)
James Brady was a mid twentieth-century Indigenous political organiser, trapper, prospector, writer, and intellectual. He was also a prolific photographer. This article considers the significance and aesthetics of Brady’s photographic archive through the lens of Indigenous visual sovereignty. Brady was Métis - one of Canada’s three recognised Indigenous peoples along with First Nations and Inuit. The Métis engaged in two conflicts with the Canadian state and negotiated the entry of a province into confederation. For a significant period of history, they lived outside Canadian infrastructures, whether the system of First Nations’ reserves created in the post-treaty era or Euro-Canadian settlements. Particularly vulnerable to land loss and displacement, the Métis were in desperate condition when Brady first began travelling with his camera. Brady’s photographs document the political rebirth of Métis people and the resilience and persistence of Métis communities in northern Alberta and Saskatchewan. They bear photographic witness to the lived experience of sovereignty rooted to place and continue to resonate with his subjects and their descendants
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Close Encounters: The Next 500 Years - Farrell Racette, Sherry. (Plug In Editions., 2011)
Catalogue d'exposition publié à l'occasion de l'exposition tenue au Plug In Institute of Contemporary Art, Urban Shaman Contemporary Aboriginal Art, et Winnipeg Art Gallery, du 22 janvier au 8 mai 2011. Now is the moment to reconfigure our notions of time to reveal alternative ways of thinking and being for the future. In Close Encounters: The Next 500 Years Indigenous artists imagine the future within the context of present experiences and past histories. By radically reconsidering encounter narratives between native and non-native people, Indigenous prophecies, possible utopias and apocalypses, this exhibition proposes intriguing possibilities for the next 500 years. "We all in different measure have carved out the future," observes Hopi photographer and filmmaker, Victor Masayesva, in his book Husk of Time. "We are all clairvoyants, soothsayers, prophets, knowingly assuming our predictions. Close Encounters brings together over 30 Indigenous artists from across Canada, the United States, South America, Europe, Australia and New Zealand, including newly commissioned work from Rebecca Belmore, Faye HeavyShield, Kent Monkman, and Edward Poitras. Jimmie Durham's sculptural work A Pole to Mark the Centre of the World (at Winnipeg) will be an ongoing critique of widely held ideas surrounding space and location, while James Luna's poignant installation The Spirits of Virtue and Evil Await my Ascension, addresses issues of ritual and the passing of time. Close Encounters showcases artists and artworks that collectively invent provocative futures from a diversity of perspectives and practices. With its myriad histories, trajectories, tensions, collisions, and self-image(s), the city of Winnipeg offers an intriguing juxtaposition for these artistic mediations. Close Encounters: The Next 500 Years presents international Indigenous perspectives in a city that in many ways also epitomizes the future of Aboriginal people in Canada. Works in multiple venues throughout the city will serve as catalysts to invent different ways of thinking, acting, and being in the world of our shared future. At this pivotal moment in time, Close Encounters invites engagement with the speculative, the prophetic, and the unknown
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé